Medical applications and prospects of polylactic acid materials - Zhenqi Yang; Guoyong Yin; Shuyang Sun; Ping Xu (iScience)
Summary: Polylactic acid (PLA) is a biodegradable and bio-based polymer that has gained significant attention as an environmentally friendly alternative to traditional petroleum-based plastics. In clinical treatment, biocompatible and non-toxic PLA materials enhance safety and reduce tissue reactions, while the biodegradability allows it to breakdown over time naturally, avoiding a second surgery. With the emergence of nanotechnology and three-dimensional (3D) printing, medical utilized-PLA has been produced with more structural and biological properties at both micro and macro scales for clinical therapy. This review summarizes current applications of the PLA-based biomaterials in drug delivery systems, orthopedic treatment, tissue regenerative engineering, and surgery and medical devices, providing viewpoints regarding the prospective medical utilization.